Full wave analysis of a superconducting stripline with large width-to-separation ratio - Yeap K.H.; Tham C.Y.; Yeong K.C.; Woo H.J.; Chong K.H. (2023)
This paper presents a full-wave analysis on the wave propagating in a superconducting stripline with a large width-to-separation ratio. A set of transcendental equation is derived, by matching the ratio of the tangential electric and magnetic fields, respectively, with the surface impedance of the strip. The propagation constant can be obtained by substituting the complex conductivity of the superconducting strip into the equation and numerically solving for the root. We have computed the attenuation constant and phase velocity using our method and compared with the analytical equation formulated by Matick using the general transmission line model, which is applied by Kautz in a superconducting stripline. The results for both methods agree exceedingly well. 2009 IEEE.